Efforts to Increase People's Knowledge Through Counseling in Realizing Healthy Homes - Riska Prasetiawati; Fatimah Nasution; Novriyanti Lubis (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Healthy homes are characterized by a healthy environment and accompanied by supporting facilities such as the availability of good air sources, besides that the behavior of residents in creating healthy homes is also one of the most important factors. Tanobato Village and Pasar Lama are the locations for the 2022 PKM held by pharmacy, Garut University. One of the flagship programs carried out by the PKM team is to provide education through socialization on how to create a healthy home in order to create a society that is physically and mentally healthy. The activity was preceded by a pre-test, material debriefing both directly and virtual counseling, and post-test to find out the extent to which residents' knowledge of the material provided was increased. The results of the counseling and survey showed that as many as 84 (73.3%) houses belonged to the category of decent houses in terms of physical conditions, a total of 74 (64.9%) houses based on basic sanitation including healthy house criteria, and 84 (73.3%) residents have the behavior to create a healthy home. Through this activity, awareness of the community's awareness to create a healthy home is getting higher.